2022
DOI: 10.1038/s41467-022-29987-x
|View full text |Cite
|
Sign up to set email alerts
|

Corrosion as the origin of limited lifetime of vanadium oxide-based aqueous zinc ion batteries

Abstract: Aqueous zinc ion batteries are receiving increasing attention for large-scale energy storage systems owing to their attractive features with respect to safety, cost, and scalability. Although vanadium oxides with various compositions have been demonstrated to store zinc ions reversibly, their limited cyclability especially at low current densities and their poor calendar life impede their widespread practical adoption. Herein, we reveal that the electrochemically inactive zinc pyrovanadate (ZVO) phase formed o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

6
67
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 218 publications
(73 citation statements)
references
References 54 publications
6
67
0
Order By: Relevance
“…Among them, vanadium oxides (such as V 2 O 5 , VO 2 , V 2 O 3 ) are considered as the promising storage host due to the abundant valence state to achieve high specific capacity, and open-frameworks assembled by various coordination polyhedral to facilitate the efficient ion storage during the electrochemical cycling [13,14]. However, it has been found that such aqueous zinc-vanadium oxide battery in the acidic electrolyte usually suffers from insufficient rate performance and poor cycle lifespan (< 3000 cycles) in the research, which greatly hinders their practical applications [15,16]. Generally, it should be a system problem that causes the electrochemical failure of aqueous zinc-vanadium oxide battery, as shown in Scheme 1, the adverse factors can be mainly divided into the following two concerns.…”
Section: Introductionmentioning
confidence: 99%
“…Among them, vanadium oxides (such as V 2 O 5 , VO 2 , V 2 O 3 ) are considered as the promising storage host due to the abundant valence state to achieve high specific capacity, and open-frameworks assembled by various coordination polyhedral to facilitate the efficient ion storage during the electrochemical cycling [13,14]. However, it has been found that such aqueous zinc-vanadium oxide battery in the acidic electrolyte usually suffers from insufficient rate performance and poor cycle lifespan (< 3000 cycles) in the research, which greatly hinders their practical applications [15,16]. Generally, it should be a system problem that causes the electrochemical failure of aqueous zinc-vanadium oxide battery, as shown in Scheme 1, the adverse factors can be mainly divided into the following two concerns.…”
Section: Introductionmentioning
confidence: 99%
“…Accordingly, rechargeable aqueous Zn metal batteries (AZMBs) are receiving increasing attention from the battery community. In addition, metallic Zn has other benefits: low cost, environmental benignity, and compatibility with slightly acidic or near-neutral aqueous electrolytes (pH close to 7). It also accommodates various cathode combinations, such as MnO 2 , V 2 O 5 , and I 2 . However, metallic Zn suffers from dendrite growth, parasitic side reactions (represented by the hydrogen evolution reaction, HER), corrosion, and the formation of unfavorable byproducts, which all jointly impair the sustainable and reliable operation of AZMBs. …”
Section: Introductionmentioning
confidence: 99%
“…In the past decades, various vanadate nanomaterials have drawn significant attention due to their good performance in batteries, catalysts, , and optical devices. , Due to the abundant calcium resource and diversity of the crystal structure, calcium vanadates have attracted great research interests. Up to now, various calcium vanadate micro/nanomaterials have been reported, such as CaV 2 O 7 , CaV 2 O 6 , CaV 4 O 9 , Ca 3 (VO 4 ) 2 , Ca 10 V 6 O 25 , CaV 2 O 5 , and CaV 3 O 7 . Considering the multivalence of vanadium and the layered structural characteristics, calcium vanadates may be promising electrode materials. However, the research on the application of calcium vanadate materials in lithium/sodium/zinc-ion batteries started late.…”
Section: Introductionmentioning
confidence: 99%